PERBEDAAN KADAR PSA DAN TGF-β1 TERHADAP PEMBERIAN KOMBINASI INHIBITOR 5α-REDUKTASE (DUTASTERIDE) DAN ANTI ESTROGEN (TAMOXIFEN) PADA PASIEN BPH LUTS - Prasetyo, Rachmat Budi; Soetojo, Soetojo; Soebadi, Doddy M (Indonesian Urological Association, 2008)
Objective: To compare the PSA and TGF-β1 plasma level before and after administration of a 5α-reductase inhibitor (dutasteride) and an anti estrogen (tamoxifen) in nonobstructive patients with BPH. Material and Method: We enrolled 40 patients with a diagnosis of BPH without urinary retention. Patients were allocated into 4 groups of 10 patients and were given tamoxifen, dutasteride, a combination of tamoxifen and dutasteride, or placebo. We measured PSA and TGF-β1 plasma levels at study entry and 3 months after administration. Data were analysed using SPSS 12. Results: Increase of TGF-β1, as high as 54% (2,18 ± 0,88 to 3,36 ± 1,06) in the tamoxifen group, 26% (2,75 ± 0,62 to 3,47 ± 0,82) in the dutasteride group, and 92% (2,37 ± 0,75 to 4,56 ± 1,98) in the combination group, was significant (p < 0,05). PSA was not significantly decreased in all groups (p > 0,05). PSA decreased 28% (4,25 ± 3,28 to 3,06 ± 3,08) in the tamoxifen group, 27% (2,20 ± 2,17 to 1,60 ± 0, 982) in the dutasteride group, and 19% (2,95 ± 1,22 to 2,40 ± 1,78) in the combination group. In the placebo group was no significant difference of both parameters. Conclusion: TGF-β1 was significantly increased in all groups except in placebo. PSA was decreased in all groups but not significant statistically. We concluded that TGF-β1 may better be used as a biomarker in the evaluation and management of BPH than PSA.